TENCON 2011 - 2011 IEEE Region 10 Conference 2011
DOI: 10.1109/tencon.2011.6129270
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of cognition using EEG: A review and a new approach

Abstract: Understanding the secrets underlying the brain functioning would be the noble achievement of this era. Learning how brain learns would be the milestone to guide the researchers of artificial intelligence, neurology and psychology. With the advent of "Integrate and Fire" model of neuron proposed about a hundred years ago, the brain research has picked up its pace in the study of different aspects of brain functionality. Many cogni tive architectures have been proposed with an aim of simulating and understanding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 30 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…It has been found that distraction and fatigue are two main sources for driver's inattention, which is considered as a strong cause for most traffic accidents [63]. Various types of measures have contributed in determining the driver's cognitive state [64][65][66]. Uses of EEG signals for fatigue detection have been widely studied in [67], while [68] has discussed the utilization of workload index to assess the driver's mental state.…”
Section: Neuroergonomics and Smart Environmentmentioning
confidence: 99%
“…It has been found that distraction and fatigue are two main sources for driver's inattention, which is considered as a strong cause for most traffic accidents [63]. Various types of measures have contributed in determining the driver's cognitive state [64][65][66]. Uses of EEG signals for fatigue detection have been widely studied in [67], while [68] has discussed the utilization of workload index to assess the driver's mental state.…”
Section: Neuroergonomics and Smart Environmentmentioning
confidence: 99%
“…EEG can also be used to investigate the effects of various stimuli on the brain, including sensory input like smell, sound, and light, or cognitive tasks like problem-solving or decision-making [14,15]. In addition, it has been used to recognize emotions and represent cognitive functions such as distraction, fatigue, and concentration [16][17][18][19]. Alarcao and Fonseca reported an emotion estimation survey using EEG signals to detect unconscious emotions from EEG signals [20].…”
Section: Methods For Estimating Psychological Statesmentioning
confidence: 99%
“…They can analyze the impact of workload mental fatigue as well as the task time on EEG features 38 . Different measures have helped for finding the driver's cognitive state [39][40][41] . Alcoholic drivers could be characterized using EEG signals of brain [42][43][44] .…”
Section: Applications In Healthcare Fieldmentioning
confidence: 99%